"Too Much to Hope": Analyzing Clergy Rhetoric on White Supremacy - Gilliland, Claire Chipman (Journal for the scientific study of religion, 2023)
As Du Bois observed a century ago, the White Church as an institution is largely associated with maintaining the status quo of racial stratification rather than offering a progressive force. To analyze the rhetoric of predominantly White clergy on race, I analyze a sample of sermons from predominantly White congregations in Charlottesville, VA following the 2017 White supremacist rally (N = 87 sermons from 38 congregations). I find that clergy draw on individualistic, other-worldly, and structural frameworks to explain the causes of and solutions to racism and racial violence. These frameworks carry different consequences; individualistic explanations are associated with calls for self-examination and prayer, while seeing racism as a battle between forces comes limited individual engagement. Further, these frameworks are overlapping within the sermons, clouding the appropriate responses to racial violence. As a whole, these responses largely affirm Du Bois’ low expectations for the White Church in combatting racism and inequality.